Plasma Concentration of Cortisol Negatively Associates with Platelet Reactivity in Older Subjects - Karolczak, Kamil; Konieczna, Lucyna; Soltysik, Bartlomiej; Kostka, Tomasz; Witas, Piotr Jakub; Kostanek, Joanna; Baczek, Tomasz; Watala, Cezary (International journal of molecular sciences, 2022)
The interaction of platelets with steroid hormones is poorly investigated. Age is one of the factors that increase the risk of pathological platelet reactivity and thrombosis. The aim of this study was to assess whether there were associations between platelet reactivity and plasma cortisol levels in volunteers aged 60–65 years. For this purpose, impedance aggregometry in whole blood measured after arachidonic acid, collagen, or ADP stimulation was used to estimate platelet reactivity and mass spectrometry was used to measure peripheral plasma cortisol concentration. Statistically significant negative correlations were observed between cortisol concentration and platelet reactivity in response to arachidonic acid and ADP, but not to collagen. The presented results suggest for the very first time that cortisol is a new endogenous modulator of platelet reactivity in the elderly population.